2023
DOI: 10.1371/journal.pone.0271939
|View full text |Cite
|
Sign up to set email alerts
|

Dengue seroprevalence study in Bali

Abstract: Introduction Dengue infection poses significant public health problems in tropical and subtropical regions worldwide. The clinical manifestations of dengue vary from asymptomatic to severe dengue manifestations. This serological survey highlighted the high incidence of asymptomatic cases. This study aimed to determine the prevalence of dengue in healthy and ill adults in Bali. Methods Cross-sectional seroprevalence surveys were performed between July 2020 and June 2021 among healthy and ill adults in Denpasa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
1
0
Order By: Relevance
“… 49 2019 A 0.037 (0.021, 0.061) PanBio dengue IgG indirect elisa kit (Abbott) Indonesia Denpasar Bali 0–40+ 2 539 indirect IgG ELISA Masyeni et al. 43 Jul 2020–Jun 2021 A 0.036 (0.011, 0.081) Panbio, Lubecl, Germany Indonesia Simpang Kiri (in Subulussalam, Nanggroe Aceh Darussalam) 0–18 18 106 indirect IgG ELISA Tam et al. 50 Oct–Nov 2014 A 0.126 (0.096, 0.162) Panbio dengue IgG ELISA Indonesia Medan Denai (in Medan, Sumatera Utara) 0–18 18 107 indirect IgG ELISA Tam et al.…”
Section: Resultsmentioning
confidence: 99%
“… 49 2019 A 0.037 (0.021, 0.061) PanBio dengue IgG indirect elisa kit (Abbott) Indonesia Denpasar Bali 0–40+ 2 539 indirect IgG ELISA Masyeni et al. 43 Jul 2020–Jun 2021 A 0.036 (0.011, 0.081) Panbio, Lubecl, Germany Indonesia Simpang Kiri (in Subulussalam, Nanggroe Aceh Darussalam) 0–18 18 106 indirect IgG ELISA Tam et al. 50 Oct–Nov 2014 A 0.126 (0.096, 0.162) Panbio dengue IgG ELISA Indonesia Medan Denai (in Medan, Sumatera Utara) 0–18 18 107 indirect IgG ELISA Tam et al.…”
Section: Resultsmentioning
confidence: 99%
“…In our study, which included individuals over 18 years of age, we did not find any significant difference in seropositivity by age group. However, studies conducted in hyperendemic areas have found an association with age and attribute it to the fact that the longer people reside in a dengue-endemic region, the greater their risk of exposure, coupled with the lifelong persistence of anti-DENV antibodies [28,29]. In the city of Santa Fe, where the first severe dengue outbreak occurred in 2016 [5], all age groups studied have been exposed to the outbreaks that have occurred since then.…”
Section: Discussionmentioning
confidence: 99%